Electrical Characterization of II-VI Thin Films for Solar Cells Application - Farhan Ahmad; Nadir Qurban; Zain Fatima; Toqeer Ahmad; Iqra Zahid; Ahmad Ali; Sehrish Rana Rajpoot; Muhammad Wasim Tasleem; Esha Maqbool (ASEAN Journal of Science and Engineering, 2022)
Cds and CdTe both are effective absorber semiconductors for thin-film solar cells. It is a naturally n-type material, which has a direct bandgap value of 2.42 eV at room temperature It has great importance in light detectors in this work, CdS thin films (TF) were synthesized on glass substrates by RF Magnetron sputtering technique in an inert gas atmosphere. The electrical properties of CdS were characterized by the Van Der Pauw method. The films showed p-type conductivity, while the films deposited at different annealed times exhibited n-type conductivity. The resistivity of the CdTe films decrease as the conductivity increased. As the source rate was increased, the hole concentration in the as-grown p-type CdTe films increased. It was also reported annealing process affects the electrical properties. Al doping CdS the value of resistivity becomes minimum as the resistivity becomes maximum although mobility has maximum value after an increase in Al doping the mobility value. As a result, the CdS/CdTe thin-film showed enhanced electrical properties for solar cell applications.